Morphological differentiation and body composition in female judokas and female weightlifters in relation to the performed sport discipline - Burdukiewicz, A.; Pietraszewska, J.; Witkowski, K.; Andrzejewska, J.; Stachon, A.; Chromik, K.; Maslinski, J. (Archives of Budo, 2010)
The phenotype body reaction to the long-lasting and intensive training in the various sport disciplines may differ. It is related to the adaptive changes in both morphological features and tissue relationship. In one hand it improves sport efficiency, but in the other it creates a threat of injuries and permanent abnormalities in body posture. This research aimed to verify the hypothesis that specialist training triggers body build-oriented changes including those in proportions of tissue components in athletes. The verification of the hypothesis will enable to plan the training load better. Material/Methods: The results of anthropometric measurements of female judokas (n=28) and female weightlifters (n=28) were analysed. The following somatic features were examined in female competitors, who participated in Polish Championships: body height and mass, circumferences of the upper and lower extremities, thickness of the skinfolds, fat mass, muscle mass and nonmuscle mass of fat-free mass. Basic statistics, significance of differences and correlation tests were applied. The development level of separate tissue components was presented on trilinear plot. Results: The conducted analysis revealed that, the level of lean body mass development in female judokas, in comparison to female weightlifters, was higher. However, female weightlifters revealed higher means of body mass and skinfolds thickness, which was related to the greater extremities circumference in those subjects. In comparison to female judokas they also characterised with greater content of fat and muscle mass. Conclusions: The distinctiveness of long-lasting and well-oriented training in different sport disciplines is reflected in differences in body build and tissue composition in subjects performing these sports.